2000
DOI: 10.1093/emboj/19.12.3142
|View full text |Cite
|
Sign up to set email alerts
|

A novel shuttling protein, 4E-T, mediates the nuclear import of the mRNA 5' cap-binding protein, eIF4E

Abstract: The eukaryotic translation initiation factor 4E (eIF4E) plays an important role in the control of cell growth. eIF4E binds to the mRNA 5¢ cap structure m 7 GpppN (where N is any nucleotide), and promotes ribosome binding to the mRNA in the cytoplasm. However, a fraction of eIF4E localizes to the nucleus. Here we describe the cloning and functional characterization of a new eIF4E-binding protein, referred to as 4E-T (eIF4E-Transporter). We demonstrate that 4E-T is a nucleocytoplasmic shuttling protein that cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
201
0
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(215 citation statements)
references
References 80 publications
7
201
0
2
Order By: Relevance
“…eIF4E can mediate nuclear export of the cyclin D1 mRNA (Rousseau et al, 1996). Entry of eIF4E into the nucleus appears to be mediated by 4E-T (Dostie et al, 2000), which contains a similar eIF4E-binding motif to that in 4E-BP1. Therefore, binding of 4E-BP1 to eIF4E could prevent eIF4E entering the nucleus, potentially affecting the transport of the cyclin D1 mRNA into the cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…eIF4E can mediate nuclear export of the cyclin D1 mRNA (Rousseau et al, 1996). Entry of eIF4E into the nucleus appears to be mediated by 4E-T (Dostie et al, 2000), which contains a similar eIF4E-binding motif to that in 4E-BP1. Therefore, binding of 4E-BP1 to eIF4E could prevent eIF4E entering the nucleus, potentially affecting the transport of the cyclin D1 mRNA into the cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…We showed that after 4 hours of hypoxia the disruption of eIF4F may also occur as a result of redistribution of eIF4E and the eIF4E translocator protein (4E-T) into either the nucleus or the recently discovered cytoplasmic bodies of mRNA processing (P-bodies; refs. 79,80). Translocation of eIF4E into either of these cellular locations makes it unavailable to participate in translation initiation.…”
Section: Mtor-independent Regulation Of Eif4fmentioning
confidence: 99%
“…In the nucleus, the monomeric form of eIF4E colocalizes with splicing factors in nuclear speckles, 18 suggesting a possible role in mRNA processing. Available data indicate that eIF4E binds capped transcripts in the nucleus following the pioneering round of translation, or in the cytoplasm.…”
Section: Translation Initiation Apparatusmentioning
confidence: 99%